Diquat poisoning, maybe another cause of osmotic demyelination syndrome: case report and literature review - Wenfu Li; Hui Zhou (Frontiers in Medicine)
Diquat (1,1′-ethylene-2,2′-bipyridine), a non-selective herbicide with significant human toxicity, is increasingly used as a substitute for paraquat in weed management practices in China. Diquat intoxication is typified by multiple organ dysfunction syndrome (MODS), predominantly manifesting as acute renal and hepatic injury, and frequently resulting in central nervous system (CNS) impairment with a poor prognosis in severe instances. Despite the rising incidence of diquat poisoning, the imaging characteristics of diquat-induced toxic encephalopathy remain inadequately documented in the literature. In this report, we present a distinctive case involving a female pediatric patient who exhibited MODS affecting the neurologic, renal, hepatic, cardiac, and gastrointestinal systems, in conjunction with rhabdomyolysis. Magnetic resonance imaging (MRI) revealed multiple abnormal signals in the pons, bilateral brachium pontis, thalamus, caudate nucleus, putamen, posterior part of the external capsule, and posterior limb of the right internal capsule. These findings are consistent with the imaging characteristics of osmotic demyelination syndrome (ODS), which is under-recognized but important. After comprehensive systemic treatment, the patient was discharged on the 30th day post-admission.